2022
DOI: 10.1021/acs.jpcc.2c06212
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Imaging and Computational Modeling Reveal That Thiophene Complexation with Co(II)porphyrin/Graphite Is Highly Cooperative

Abstract: Scanning tunneling microscopy (STM) was employed to quantitively investigate in situ binding of 3-phenyl thiophene (PhTh) to Co­(II)­octaethyl porphyrin (CoOEP) supported on highly ordered pyrolytic graphite (HOPG) in fluid solution. To our knowledge, this is the first single-molecule level study of a complexation reaction between a metalloporphyrin and a sulfur base at the solution/solid interface and one of the few examples of thiophene coordination with a d7 transition metal. Real-time imaging experiments r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…[21][22][23] The origin of this model stems from the elaborate work and thermodynamic models previously developed for the processes in solution. 20 More recently, the work of Hipps et al has shown that there is a small degree of cooperativity in the binding of small ligands such as methoxypyridine, 1-phenylimidazole or 3-phenylthiophene to a self-assembled network of cobalt(II) octaethylporphyrin (CoOEP) at the 1-phenyloctane/HOPG interface, [24][25][26] While adsorption overall appears to follow a Langmuir isotherm, which would suggest no cooperativity, comparing the fraction of adjacent bound CoOEP molecules with the fraction that would be obtained from a random distribution indicates that cooperativity is present. Additionally, the same group has presented a computational study to determine position-dependent desorption energies for coronene on Au(111) and HOPG as substrates by utilizing the nearest neighbour interaction energy model and showed that it performs well for systems showing weak adsorbate-substrate cooperativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] The origin of this model stems from the elaborate work and thermodynamic models previously developed for the processes in solution. 20 More recently, the work of Hipps et al has shown that there is a small degree of cooperativity in the binding of small ligands such as methoxypyridine, 1-phenylimidazole or 3-phenylthiophene to a self-assembled network of cobalt(II) octaethylporphyrin (CoOEP) at the 1-phenyloctane/HOPG interface, [24][25][26] While adsorption overall appears to follow a Langmuir isotherm, which would suggest no cooperativity, comparing the fraction of adjacent bound CoOEP molecules with the fraction that would be obtained from a random distribution indicates that cooperativity is present. Additionally, the same group has presented a computational study to determine position-dependent desorption energies for coronene on Au(111) and HOPG as substrates by utilizing the nearest neighbour interaction energy model and showed that it performs well for systems showing weak adsorbate-substrate cooperativity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while the concept of cooperativity has been observed as important in determining the type of network observed on the surface 36,37 and evaluated for several examples, 21,24,[26][27][28]38 a deeper quantitative understanding and thermodynamic investigation of the effect of cooperativity in the formation of SAMNs is still missing.…”
Section: Introductionmentioning
confidence: 99%